(untitled) (Damascus University Journal for legal sciences, 2024)
With the advent of the steam engine and powered machines, human life began to adopt an accelerated pattern that changed the ways of human life, and the field of communications gained its largest share of the wheel of development after the invention of the mobile phone and then the Internet, and this development was reflected in the means of communication on various aspects of human life, so life became more Luxury, stability and speed, but at the same time and with these advantages, the matter was not without risks and negatives. As various aspects of human life, and although the use of modern technologies enjoys a good reputation among many of its supporters, due to its multiple benefits, but as the process of accessing science and knowledge has become less difficult, and geographical distances between countries have been reduced and time has been saved thanks to these technologies, on the other hand, it is not possible to accurately determine The extent of its negative effects, and this applies to the use of modern means of communication in judicial procedures in general and criminal procedures in particular, and here comes the role of the idea of ​​public order in controlling and defining the legal rules that limit the largest possible form of these negatives and risks to the procedural justice system in criminal cases.